European recommendations on the proper indication and use of peripheral venous access devices (the ERPIUP consensus): A WoCoVA project. Issue 1 (January 2023) - Pittiruti, Mauro; Van Boxtel, Ton; Scoppettuolo, Giancarlo; Carr, Peter; Konstantinou, Evangelos; Ortiz Miluy, Gloria; Lamperti, Massimo; Goossens, Godelieve Alice; Simcock, Liz; Dupont, Christian; Inwood, Sheila; Bertoglio, Sergio; et al.
Since several innovations have recently changed the criteria of choice and management of peripheral venous access (new devices, new techniques of insertion, new recommendations for maintenance), the WoCoVA Foundation (WoCoVA = World Conference on Vascular Access) has developed an international Consensus with the following objectives: to propose a clear and useful classification of the currently available peripheral venous access devices; to clarify the proper indication of central versus peripheral venous access; discuss the indications of the different peripheral venous access devices (short peripheral cannulas vs long peripheral cannulas vs midline catheters); to define the proper techniques of insertion and maintenance that should be recommended today. To achieve these purposes, WoCoVA have decided to adopt a European point of view, considering some relevant differences of terminology between North America and Europe in this area of venous access and the need for a common basis of understanding among the experts recruited for this project. The ERPIUP Consensus (ERPIUP = European Recommendations for Proper Indication and Use of Peripheral venous access) was designed to offer systematic recommendations for clinical practice, covering every aspect of management of peripheral venous access devices in the adult patient: indication, insertion, maintenance, prevention and treatment of complications, removal. Also, our purpose was to improve the standardization of the terminology, bringing clarity of definition, and classification.